Influence of the Medial Malleolus Osteotomy on the Clinical Outcome of M-BMS + I/III Collagen Scaffold in Medial Talar Osteochondral Lesion (German Cartilage Register/Knorpelregister DGOU). (December 2021) - Gottschalk, Oliver; Baumbach, Sebastian Felix; Altenberger, Sebastian; Körner, Daniel; Aurich, Matthias; Plaass, Christian; Ettinger, Sarah; Guenther, Daniel; Becher, Christoph; Hörterer, Hubert; Walther, Markus
Objective: Osteochondral lesions of the talus are common injuries, with one of the leading treatment options being the M-BMS (matrix-augmented bone marrow stimulation) + I/III collagen scaffold. Osteotomy of the medial malleolus is not unusual but presents the risk of malunion or irritation by hardware. The aim of the study was to analyze data from the German Cartilage Society (Knorpelregister DGOU) to evaluate the influence of medial malleolar osteotomy on clinical results of M-BMS + I/III collagen scaffold. Design: The ankle module of the Cartilage Register includes a total of 718 patients, while 45 patients met the inclusion criteria. Patients were treated with an M-BMS + I/III collagen scaffold of the medial talus, 30 without and 15 with an osteotomy of the medial malleolus. The follow-up evaluations included FAAM (Foot and Ankle Ability Measure), FAOS (Foot and Ankle Outcome Score), and VAS (visual analogue scale). Results: Forty-five patients (22 male, 23 female) aged between 18 and 69 years (mean: 34 years) were included in this study. Between preoperative and 12 months postoperative, we noted a significant improvement in FAAM-ADL (Activity of Daily Living) ( P = 0.004) as well as FAOS-Pain ( P = 0.001), FAOS-Stiffness ( P = 0.047), FAOS-ADL ( P = 0.002), FAOS-Sport ( P = 0.001), and FAOS Quality of Life ( P = 0.009). There was no significant difference between patients who underwent an osteotomy or not. Conclusion: The results show a significant improvement in patients' outcome scores following a M-BMS + I/III collagen scaffold. No statistical difference was noted among those undergoing medial malleolar osteotomy.